2017
DOI: 10.1111/jpi.12433
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against the pathological cardiac hypertrophy induced by transverse aortic constriction through activating PGC‐1β: In vivo and in vitro studies

Abstract: Melatonin, a circadian molecule secreted by the pineal gland, confers a protective role against cardiac hypertrophy induced by hyperthyroidism, chronic hypoxia, and isoproterenol. However, its role against pressure overload-induced cardiac hypertrophy and the underlying mechanisms remains elusive. In this study, we investigated the pharmacological effects of melatonin on pathological cardiac hypertrophy induced by transverse aortic constriction (TAC). Male C57BL/6 mice underwent TAC or sham surgery at day 0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 67 publications
1
64
0
Order By: Relevance
“…The usefulness of melatonin treatment for cardiovascular diseases has been reported . Melatonin supplementation protected against pathological cardiac remodeling induced by transverse aortic constriction and isoproterenol, and melatonin prevented mitochondrial fission and improved cardiac function in mice with diabetes through the SIRT1‐PGC1α pathway . Administration of melatonin in AMI patients with ST elevation, who presented early after symptom onset, was associated with a significant reduction in the infarct size and remodeling after primary percutaneous coronary intervention .…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of melatonin treatment for cardiovascular diseases has been reported . Melatonin supplementation protected against pathological cardiac remodeling induced by transverse aortic constriction and isoproterenol, and melatonin prevented mitochondrial fission and improved cardiac function in mice with diabetes through the SIRT1‐PGC1α pathway . Administration of melatonin in AMI patients with ST elevation, who presented early after symptom onset, was associated with a significant reduction in the infarct size and remodeling after primary percutaneous coronary intervention .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin, chemically N‐acetyl‐5‐methoxytryptamine, has been proved to exert its protective properties in a variety of cardiovascular diseases . Recent studies have reported that melatonin has the ability to protect against diabetes‐induced cardiac dysfunction .…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin, chemically N-acetyl-5-methoxytryptamine, has been proved to exert its protective properties in a variety of cardiovascular diseases. [11][12][13][14][15] Recent studies have reported that melatonin has the ability to protect against diabetesinduced cardiac dysfunction. 16,17 Our previous study demonstrated that melatonin alleviated posttraumatic myocardial injury and cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin exhibits a repertoire of biological functions . It has been shown to influence immune function, tumor growth, sleep‐wake cycle and circadian rhythms and provide redox homeostasis and antioxidant protection in tissues .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin exhibits a repertoire of biological functions. 47 It has been shown to influence immune function, tumor growth, sleep-wake cycle and circadian rhythms and provide redox homeostasis and antioxidant protection in tissues. [23][24][25] Moreover, a number of studies demonstrated that melatonin is implicated in the development of scoliosis.…”
Section: Melatonin Protected Against the Detrimental Effects Of Mirmentioning
confidence: 99%